Anomalies in attributed networks. - Hossein Rafieizadeh (22676722) (2025)
Structural anomaly: an unexpected inter-community bridge, where the orange node sits in the cut between two communities and forms a shortcut (dashed) edge to the right cluster. Attribute anomaly: the orange node’s feature vector (colored bars) deviates from those of its neighbors even though its connectivity looks normal. Interaction anomaly: a structure–attribute mismatch, where the orange node’s attributes align with the left community while its links embed it in the right community. Visual encoding: blue = normal nodes and edges; orange = anomalous node or edge; dashed orange edge = anomalous link; colored bars = node attributes.